Multimodal Semiotic Analysis of Coldplay’s Viva La Vida: Lyrical, Visual, And Intertextual Meaning - Pudjiati, Danti; Mawarni, Venti; Urassa, Bariki; Hamdani, Haris (LPPM STKIP Kusuma Negara, 2025)
This study analyzes Viva La Vida by Coldplay to explore the deeper meaning behind its lyrics and music video.The song tells the story of a fallen king and expresses themes like power, loss, regret, and hope. As a multimodal text, it combines music, words, and visuals to deliver its message. Using a qualitative method, the researcher closely examined the lyrics and visuals.The analysis is based on three main theories: Barthes’ semiotics, Kristeva’s intertextuality and Kress & van Leeuwen’s multimodality. Barthes’ theory helps explain how words like “crown” and “puppet” carry not just literal meaning, but also feelings and cultural ideas. Kristeva’s intertextuality shows how the song connects with older stories from history, the Bible, and literature, such as the French Revolution and Shakespeare. These references give the song deeper emotional value.The music video supports the story through strong visual symbols like a dying rose, broken television, and gestures of surrender. According to Kress and van Leeuwen, these elements add to the overall meaning. In the end, Viva La Vida gives a clear message: power does not last forever, but people can learn and reflect.The song is also useful for learning English grammar, vocabulary, and critical thinking